Пути повышения эффективности компьютерного моделирования режимов работы электрических систем на основе уравнений в фазных координатах - Веприк, Ю.Н. (Електротехніка і електромеханіка, 2017)
Показаны необходимость перехода к разработке моделей на основе уравнений в фазных координатах и возможности
повышения эффективности таких разработок за счет использования неявных методов интегрирования, перехода на
более высокий уровень декомпозиции и унификации разрабатываемых моделей Показані необхідність переходу до розробки моделей на основі рівнянь у фазних координатах і можливості підвищення ефективності таких розробок за рахунок використання неявних методів інтегрування, переходу на більш високий
рівень декомпозиції і уніфікації моделей, що розробляються. The development of electrical systems must be accompanied by
the development of tools and their modeling. However, the possibility of development models, traditionally developed on the
basis of the transition from the real to the single-phase threephase circuits equivalents, represented exhausted. Therefore,
along with the use of single-phase three-phase equivalents need
to develop models in phase coordinates. Showing the need to
move to the development of models based on equations in the
phase coordinates and the possibility of increasing the effectiveness of development through the use of implicit methods of integration, the transition to a higher level of decomposition and
unification models developed for the implementation of the
structural approach to modeling complex systems